Studi Kasus: Pengaruh Edukasi Penerapan Diet Diabetes Mellitus Terhadap Pengetahuan dan Kepatuhan Pada Pasien Diabetes Mellitus Tipe II - Sitti Nenti Sarifah Sundari; Resti Yulianti Sutrisno (Jurnal Sains dan Kesehatan, 2023)
The number of diabetes mellitus from year to year is increasing if no management is carried out will cause complications and even death. Therefore, it is important for diabetes mellitus patients to know the four pillars of diabetes mellitus management. The purpose of this case study is to see knowledge and compliance related to  diabetes mellitus diet using booklet media  summarized with 4 pillars of diabetes mellitus.  The study starts May 5-6, 2023. The method in this study uses a case study approach method by applying health education counseling related to the four pillars of diabetes mellitus using a booklet. The sample in this study was a patient with type II diabetes mellitus. Data collection was conducted by interviews, health checks, pre-tests, provision of health education, and post-tests. This research instrument used questionnaires on knowledge and adherence to diabetes mellitus diet.  The results of this case study found  that there was an increase in patient knowledge and compliance after providing health education related to the 4 pillars of diabetes mellitus. Especially people with diabetes mellitus in order to avoid the risk of complications that may occur and as an effort to increase knowledge and compliance related to diabetes mellitus diet. One of the interventions that can be provided for people with diabetes mellitus is the provision of health education related to the four pillars of diabetes mellitus consisting of: diabetes mellitus education, nutritional diet, pharmacology, and physical activity training.